238 Bridging the Gap: Expanding and Improving the Role of the Integrated Care Team in a Level 4 Hospital. (16th September 2019) - Fitzpatrick, Donal; Heywood, Sarah; O'Mahony, Catherine; Gallagher, Paul
Abstract: Background: The traditional model of acute episodic care for older people is reactive and outdated. The integrated care team (ICT) was introduced in April 2017. It comprises a physiotherapist, occupational therapist, clinical nurse specialist and case manager and provides intensive rehabilitation at home to frail older adults after an acute presentation to hospital, thus bridging acute hospital care and coordinated longitudinal care in the community. Methods: We evaluated the integrated care team referral database as well as discharge letters from July to November 2018. Results: Over 5 months, 45 out of approximately 90 referrals were deemed appropriate for the ICT. Almost half of referrals were unsuitable because of medical acuity or specific instructions such as being unable to weight-bear. Over half of referrals came from the emergency department with no referrals from general surgery, orthopaedics or cardiology. During the time of review, the service was operating at <85% capacity. There is no specific registrar assigned to review ICT referrals. The service is expanding with 123 referrals in six months, compared to 54 in the same period the previous year. Conclusion: The integrated care team helps older adults to avoid hospital admission, return home sooner and regain independence and is a much-appreciated service in the area. We identified shortcomings in the referral process, formal medical oversight and awareness of the service in areas where it could provide the most value. The ICT can expand as a key asset for frail older adults if supported by the necessary resources, staffing, consultant geriatrician leadership, referral criteria and pathways and is promoted and publicized in the clinical settings where it has the greatest potential for benefit.